Ação protetora da Hesperitina sobre as alterações hematológicas induzidas mela micotoxina Zearalenona - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Zearalenone (ZEA) from the fungus Fusarium graminearum, have many toxic effects on the body. It is considered hematotóxica and take effect on the oxidant system. Thus, hesperetin, an important antioxidant found in citrus fruits, can act as an important antioxidant opposite to toxic actions of ZEA. The objective was to analyze the antioxidant action of hesperetin as a preventive factor, compared to hematological changes induced by ZEA in mice. We used 20 male Swiss mice divided into 4 groups (n = 5): Group 1 (Salina + olive oil), group 2 (hesperetin 25 mg / kg + olive oil), group 3 (Salina + ZEA 40 mg / kg) and group 4 (hesperetin 25 mg / kg + ZEA 40 mg / kg). For 10 consecutive days administered to hesperetin (50 mg / kg / day, po) and from the 11th day administered only to ZEA (40 mg / kg / day, po). After 48 hours, animal euthanasia was carried out where blood was collected by cardiac puncture. Blood samples were homogenized and analyzed with an automatic counter for the total count of RBC, WBC, MCV, MCH, MCHC, HT, HGB and platelets. After it was used the blood smear technique for differential counting of neutrophils (segmented and bats), eosinophils, basophils, lymphocytes and monocytes. Statistical analysis was performed by analysis of variance (ANOVA) of two ways. The ZEA hematotoxicity caused by increased total leukocytes, as well as increase in hemoglobin and hematocrit, and decreased the number of lymphocytes as well as erythrocytes and platelets. The pre treatment with hesperetin prevented the onset of toxic effects induced by ZEA in virtually all parameters and thus, this antioxidant may be used as an alternative in the prevention of damage by ZEA.
Keywords: Antioxidante; Hematologia; Toxicidade; Camundongos; Antioxidant; Hematology; Toxicity; Mice; CNPQ::CIENCIAS DA SAUDE